Indigenous Parents' Perspectives of Factors That Facilitate or Impede Engagement in Internet-Based Parenting Support Programs: Interpretive Description Study - Michelle L Butt; Ysabella Jayne Willett; Vicky Miller; Brenda Jacobs; Era Mae Ferron; Amy L Wright (JMIR Publications, 2024)
BackgroundParenting support programs enhance parents' health and their child's development. The COVID-19 pandemic necessitated the delivery of these programs over the internet. After the pandemic, internet-based programs are still preferred by some. ObjectiveWe aimed to understand Indigenous parents' experiences engaging in internet-based parenting support programs; thus, an interpretive description study was conducted. MethodsA total of 20 Indigenous (female, male, and Two-Spirit) parents of children aged <5 years participated in semistructured interviews; data underwent collaborative thematic analysis with Indigenous community partners informed by the Two-Eyed Seeing framework and ethical space. ResultsParents' experiences were classified into five themes: (1) Purpose: Program Delivery and Content, (2) Belonging: Building Relationships and Connections, (3) Hope: Cultural Connection, (4) Meaning: New or Improved Parenting Skills and Mental Wellness, and (5) Recommendations for Organizations. ConclusionsThe study findings can inform internet-based parenting program delivery to enhance engagement for Indigenous families.